Answer:
[tex]x(t)=\frac{1}{2}e^{-2t}+\frac{1}{2}e^{2t}[/tex]
Step-by-step explanation:
The given differential equation is [tex]x''-4x=0[/tex]
The characteristics equation is given by
[tex]r^2-4=0\\\\r^2=4\\\\r=\pm2[/tex]
Therefore, the solution of the DE is given by
[tex]x(t)=c_1e^{-2t}+c_2e^{2t}[/tex]
On differentiating, we get
[tex]x'(t)=-2c_1e^{-2t}+2c_2e^{2t}[/tex]
Apply the initial conditions
x(0)=1
[tex]1=c_1e^{0}+c_2e^{0}\\\\c_1+c_2=1...(i)[/tex]
Second condition is x'(0)=0
[tex]0=-2c_1e^{0}+2c_2e^{0}\\\\-2c_1+2c_2=0\\\\c_1-c_2=0...(ii)[/tex]
Add (i) and (ii)
[tex]2c_1=1\\\\c_1=\frac{1}{2}[/tex]
Substituting this value in (ii)
[tex]\frac{1}{2}-c_2=0\\\\c_2=\frac{1}{2}[/tex]
Hence, the solution of the DE is
[tex]x(t)=\frac{1}{2}e^{-2t}+\frac{1}{2}e^{2t}[/tex]